Pengembangan Game Edukasi Sebagai Media Pembelajaran Berbasis Android Pada Materi Bangun Ruang Kelas VII SMP Negeri 1 Geger - Rika Kusumawati Wiryaningtyas; Fatriya Adamura; Indra Puji Astuti (Mathematics Education Study Program, 2023)
This study aims to determine the level of validity, effectiveness and practicality of the development of educational games as an Android-based learning media on Building Space material. This research was conducted at SMP Negeri 1 Geger with the research subjects being class VII students. The research method used is ADDIE (Analysis, Design, Development, Implementation, Evaluation). The instruments used in this study include product validation sheets aimed at measuring the validity level of the product being developed, student response questionnaire validation sheets aimed at validating student response questionnaire sheets before being handed over to students, student response questionnaire sheets aimed at measuring the level of practicality of the product being developed as well as test questions aimed at measuring the level of effectiveness of the product being developed. The results showed that educational games as learning media based on Android met (1) valid criteria with a validity percentage of 83%, (2) practical criteria with a practicality percentage of 87.27%, (3) effective criteria with an average N-Gain of 0, 60. Based on the data obtained, it shows that educational games as learning media based on Android meet the valid, practical and effective criteria so that they are suitable for use as learning media in the mathematics learning process.